Legal Issues Concerning P2P Exchange of Educational Materials and Their Impact on E-Learning Multi-Agent Systems - Gil, Eugenio; Castillo Sanz, Andrés G (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
The last years have known an impressive change in the use of technologies for the sharing and dissemination of knowledge, thus affecting deeply all the traditional means used by education in all its shapes and levels. This transformation has not been fully understood by the society at large for its immense impacts and its short life. This paper describes in the question emerging from the clash of the rights to education in a wide sense and the rights derived from authorship and how that issue is affecting the design of e-learning multi-agent tools.
Keywords: e-learning; Education; Knowledge Management, Law; Multi-Agent Systems; IJIMAI